Reactivation of Hepatitis B Virus (HBV) Following Cancer Chemotherapy - Rahman, MM (Journal of Armed Forces Medical College, Bangladesh, 2010)
Reactivation of Hepatitis B virus (HBV) may occur after immunosuppressive therapy and cancer chemotherapy. Some of these cases may develop liver failure in a previously compensated disease. Aim of this case report is to make an awareness of this reactivation of HBV in Bangladeshi society after cancer chemotherapy or immunosuppressive therapy. A forty-five-year old lady, mother of one child was found to have positive Hepatitis B surface antigen (HBsAg) since 1994 when the test was done for vaccination. She was asymptomatic and clinically unremarkable. She was treated with standard Interferon for 24 weeks in 2000 when Alanine aminotransferase (ALT) was high, Hepatitis B envelope antigen (HBeAg) & HBV deoxyribonucleic acid (DNA) were positive. After treatment HBeAg & HBV DNA were negative and ALT was normal. She developed carcinoma of the left breast which was operated in July 2008. Combination cancer chemotherapy started. After 5th cycle of chemotherapy she developed rise of ALT (1200 i.u/L) and HBV DNA (> 105 copies/ml). Patient was treated with tablet Lamivudine 100 mg/day. After one year of follow up she had no symptoms. HBV DNA and ALT became normal. Reactivation of HBV may occur after cancer chemotherapy or immunosuppressive therapy. At present recommendation of Asian Pacific Association for Study of Liver (APASL), European Association for the Study of Liver (EASL) and American Association for the Study of Liver Diseases (AASLD) is to start prophylactic Lamivudine, Entecavir or any other antiviral drugs in all patients who are positive for HBsAg irrespective of HBeAg, ALT or HBV DNA status before starting chemotherapy or immunosuppressive therapy. So, HBsAg and Anti HBc (Hepatitis B core) should be tested in all such cases. Key words: Hepatitis B virus reactivation; chemotherapy. DOI: 10.3329/jafmc.v6i1.5991 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.34-35